Evaluation of the Projek Penguatan Profil Pelajar Pancasila for character building - Nurul Alipah; Elin Driana; Ernawati Ernawati (Inovasi Kurikulum, 2025)
The rapid advancement of technology has reshaped various dimensions of human life, requiring education systems to prepare students for complex future challenges. In Indonesia, the Pancasila Student Profile Strengthening Project (P5) was launched as a national initiative to cultivate the competencies and character necessary for students to navigate these transformations. This study evaluates the implementation of the P5 program in a public junior high school in West Jakarta using a qualitative approach and the CIPP evaluation model. Data were obtained through interviews, observations, and document analysis involving the principal, teachers, students, parents, and a school supervisor. The context evaluation revealed alignment between P5 and national education goals, although designing projects that were responsive to students’ needs and local values remained challenging. The input evaluation showed adequate facilities but uneven teacher readiness and inconsistent parental support. The process evaluation demonstrated active engagement, collaboration, and creativity, yet implementation was hindered by limited time, coordination challenges, and varied student participation. The product evaluation indicated improvements in cooperation, independence, critical thinking, and confidence, though students with limited home support faced obstacles. The study highlights the need for enhanced teacher training, stronger stakeholder collaboration, and equitable resource allocation to ensure the program’s sustainability.   Abstrak Kemajuan teknologi yang semakin pesat telah mengubah berbagai dimensi kehidupan manusia sehingga sistem pendidikan harus mempersiapkan siswa menghadapi tantangan masa depan yang semakin kompleks. Di Indonesia, Projek Penguatan Profil Pelajar Pancasila (P5) diluncurkan sebagai inisiatif nasional untuk menumbuhkan kompetensi dan karakter yang diperlukan siswa dalam menghadapi transformasi tersebut. Penelitian ini mengevaluasi pelaksanaan program P5 di sebuah sekolah menengah pertama negeri di Jakarta Barat dengan menggunakan pendekatan kualitatif dan model evaluasi CIPP. Data diperoleh melalui wawancara, observasi, dan analisis dokumen yang melibatkan kepala sekolah, guru, siswa, orang tua, dan pengawas sekolah. Evaluasi konteks menunjukkan keselarasan antara P5 dan tujuan pendidikan nasional, meskipun perancangan projek yang responsif terhadap kebutuhan siswa dan nilai lokal masih menjadi tantangan. Evaluasi input menunjukkan fasilitas memadai, tetapi kesiapan guru dan dukungan orang tua belum merata. Evaluasi proses menunjukkan keterlibatan, kolaborasi, dan kreativitas siswa, namun pelaksanaan terhambat oleh keterbatasan waktu, tantangan koordinasi, dan variasi partisipasi siswa. Evaluasi produk menunjukkan peningkatan kerja sama, kemandirian, berpikir kritis, dan kepercayaan diri, meskipun siswa dengan dukungan rumah yang terbatas menghadapi hambatan. Penelitian ini menekankan perlunya peningkatan pelatihan guru, penguatan kolaborasi antar pemangku kepentingan, dan pemerataan alokasi sumber daya untuk memastikan keberlanjutan program. Kata Kunci: Model CIPP; pembelajaran berbasis projek; pendidikan karakter; profil pelajar Pancasila; sekolah menengah pertama